Ensuring Equity in Health Services in Hospital Settings through Social Work Interventions: A Mixed Method Study - Golam Azam; Muhammad Mamunur Rashid; Abdul Mazid (Social Work and Society)
The study aimed to explore the status of equity in health service provisions and the process of ensuring equity in health services in the Social Welfare Department (SWD) of a tertiary care hospital with the application and effectiveness of social work interventions at micro and macro levels. Under pragmatism, the study employed a mixed-method approach within the explorative research framework that applied social surveys, case studies, and observations. A total of 120 poor diabetic patients for a survey, 10 patients for case studies, and 10 key informants were chosen for the study. The key findings reveal that SWD equitably distributes healthcare services through the identification of patients, assessment of psychophysical conditions, economic and social conditions, and distribution of services to the patients. The need-based and rehabilitation-based social work interventions at micro and macro levels contributed to the patients getting satisfied with the healthcare services in the hospital. In conclusion, the tertiary care services for poor diabetic patients need to be upgraded to meet their healthcare needs.